2009
DOI: 10.1002/ibd.20908
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus fermentum CECT 5716 prevents and reverts intestinal damage on TNBS-induced colitis in mice

Abstract: Pretreatment with L. fermentum CECT 5716 attenuates TNBS colitis, an effect that seems to be due to its antioxidant abilities. When administered after TNBS, this probiotic is also effective in accelerating colitis recovery, and this is associated with an enhanced Toll-like receptor function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…infantis (304), and Streptococcus thermophilus ST28 (320). Additional studies have demonstrated the ability of several probiotic species to reduce the expression of the Th17-promoting cytokines IL-6 and IL-23 (243) in vitro as well as in mouse models of liver fibrosis and GI permeability (188) and colitis (321)(322)(323). Further mechanisms of probiotic modulation of Th17 cell differentiation may include the inhibition of the costimulatory molecules CD40 and CD80 on intestinal epithelial cells or the downregulation of the Th17-promoting transcription factors ROR␥T, STAT3, and NF-B (243).…”
Section: Protective Mechanisms Of Probiotics Against Ulcerative Colitismentioning
confidence: 99%
“…infantis (304), and Streptococcus thermophilus ST28 (320). Additional studies have demonstrated the ability of several probiotic species to reduce the expression of the Th17-promoting cytokines IL-6 and IL-23 (243) in vitro as well as in mouse models of liver fibrosis and GI permeability (188) and colitis (321)(322)(323). Further mechanisms of probiotic modulation of Th17 cell differentiation may include the inhibition of the costimulatory molecules CD40 and CD80 on intestinal epithelial cells or the downregulation of the Th17-promoting transcription factors ROR␥T, STAT3, and NF-B (243).…”
Section: Protective Mechanisms Of Probiotics Against Ulcerative Colitismentioning
confidence: 99%
“…Subsequent studies revealed that this strain was a good probiotic candidate since it reached high survival rates when exposed to gastrointestinal tract-like conditions, showed a strong adherence to intestinal cells, stimulated the expression of mucin-encoding genes, produced antimicrobial compounds, and displayed in vivo and in vitro immunomodulatory and antibacterial properties against pathogenic bacteria (1,5,7). L. fermentum CECT 5716 showed a beneficial effect in a murine model of intestinal inflammation, reducing the inflammatory response and the intestinal damage (2). In addition, consumption of this strain enhances the response to influenza vaccination in healthy volunteers and reduces the incidence of influenza-like illness (8).…”
mentioning
confidence: 99%
“…Most commonly tested potential probiotics are lactobacillus strains that possess the plethora of highly desirable properties related to host health. Lactobacillus fermentum has long been studied for its probiotic properties because of its human origin, adherence capacity in GI tract, as well as protection in animal models of bowel inflammation (26,27). Experimental data also support its role in mucosal barrier fortification (28).…”
Section: Discussionmentioning
confidence: 99%